Transforming talent management as a game changer for firm competitiveness of Islamic banks - Sudarmawan Samidi; Mohammad Syamsul Maarif; Imam Teguh Saptono; Laily Dwi Arsyianti (Cogent Business & Management, 2023)
Organizations have begun to realize how important talent management is for improving firm competitiveness. However, talent management is seen being uncommon in Islamic financial institutions. In addition, since Maqasid Shariah is the foundation upon which Islamic financial institutions are operated, Maqasid Shariah values must also be reflected in talent management. The study aims to examine the role of talent management (TM), Maqasid Shariah (MS), leadership, and organizational commitment (OC) in increasing the firm competitiveness of Islamic banks (IBs) in Indonesia. The study uses a quantitative approach by collecting data from 370 employees of Islamic Banks in Indonesia. The data was analyzed using Structural Equation Modeling-Partial Least Square. The finding shows that talent management has a positive impact on Maqasid Shariah, leadership, organizational commitment, while those variables also play an important role as mediating variables toward firm competitiveness. It also supports that Maqasid Shariah affect the leadership. The study provides important insight into talent management practice, particularly in the Islamic banking industry. The study also provides a reference for the management of Islamic Banks, Islamic banks practitioners, and regulatory authorities in making policies related to the talent management system to increase their competitive advantage in the disruptive era. Furthermore, academicians can use this study's findings to build curricula for higher education institutions that would better connect with industry needs and produce qualified graduates who can compete on a global scale.
Keywords: M10; M12; O15; 650; firm competitiveness; human resource; Islamic banks; Maqasid Shariah; talent management